Imperfect competition in derivatives markets - Christina Brinkmann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Since the push towards central clearing in derivatives markets after the global financial crisis, an open question has been how the development has affected competition. This paper models imperfect competition between dealers in derivatives markets. Two risk-neutral dealers offer derivatives to risk-averse clients with a hedging need, and compete in price (fee) and quality (default probability). I find that with such two-dimensional competition, for given default probabilities, an equilibrium in prices exists that is preferred by both dealers. In this equilibrium the dealer with the lower default probability makes larger profits - a feature, that can produce market discipline to keep the own default probability low. If a central counterparty (CCP) is introduced as an innovation that removes the quality dimension of the competition, this market force pushing for higher qualities vanishes.
Keywords: G12; G23; G28; L13; L15; 330; Derivatives; OTC Markets; Central Clearing; Imperfect Competition; Vertical Product Differentiation